The Influence of Work Environment and Work Dicipline on Employee Performance (A Survey of Hatchery Employees at CV. Tanjung Mulya) - Risda Febrian; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of work environment and work discipline on employee performance (a survey of hatchery employees at CV. Tanjung Mulya). This study uses a survey method. The type of data used is primary data and secondary data, with a research sample of 74 respondents from employees of the hatchery section of CV. Tanjung Mulya, and using the saturated sample method. The analytical tool used in SPSS version 25. Data collection techniques using interviews, questionnaires and documentation studies. The results showed that the work environment and work discipline simultaneously had a significant effect on employee performance. The work environment partially has no significant effect on employee performance. Work discipline partially has a significant effect on employee performance.